2016
DOI: 10.4172/2155-9562.1000357
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal CA2 Region: A New Player in Social Dysfunctions

Abstract: For social species, normal social cognitive functions are essential for individuals to survive in a social group. Various neuropsychiatric disorders, including schizophrenia, autism and bipolar disorder are characterized by the impairments in social cognition. The hippocampus has been at the forefront of research in learning and memory for several decades. Hippocampal dysfunction contributes to learning and memory impairments as well as a range of social dysfunctions. However, precise contributions of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that the hippocampus is implicated in the encoding, updating, and modulation of memory representations that underlies flexible behavior (Rubin, Watson, Duff, & Cohen, ; Wimmer & Shohamy, ). Especially, the hippocampus’ CA2 subregion, has been causally linked with social memory processes in an animal model (Hitti & Siegelbaum, ), underlining its relevance in social learning (Mou, ). Given these findings we suggest that the rTPJ–hippocampus connectivity indicates that mentalizing and memory formation processes co‐occur and underlie individual social learning during the game as further analyses showed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the hippocampus is implicated in the encoding, updating, and modulation of memory representations that underlies flexible behavior (Rubin, Watson, Duff, & Cohen, ; Wimmer & Shohamy, ). Especially, the hippocampus’ CA2 subregion, has been causally linked with social memory processes in an animal model (Hitti & Siegelbaum, ), underlining its relevance in social learning (Mou, ). Given these findings we suggest that the rTPJ–hippocampus connectivity indicates that mentalizing and memory formation processes co‐occur and underlie individual social learning during the game as further analyses showed.…”
Section: Discussionmentioning
confidence: 99%
“…While the other subunits of the hippocampus have received extensive attention, the CA2 region has been largely neglected, poorly understood, and for the most part, unexplained (Chevaleyre and Siegelbaum, 2010; Caruana et al, 2012; Cui et al, 2013; Stevenson and Caldwell, 2014). Recent evidence has shed light on the obscurities of the CA2, characterizing it as a distinct subregion, with its own unique afferents and efferents, cellular composition, and contribution to hippocampal processes (Cui et al, 2013; Dudek et al, 2016; Mou, 2016).…”
Section: The Ca2 Subregion Of the Hippocampusmentioning
confidence: 99%